Chinese postman games with repeated players - Arantza Estévez-Fernández; Herbert Hamers (Tinbergen Institute, 2018)
This paper analyses Chinese postman games with repeated players, which generalize Chinese postman games by dropping the one-to-one relation between edges and players. In our model, we allow players to own more than one edge, but each edge belongs to at most one player. The one-to-one relation between edges and players is essential for the equivalence between Chinese postman-totally balanced and Chinese postman-submodular graphs shown in Granot et al. (1999). We illustrate the invalidity of this result in our model. Besides, the location of the post office has a relevant role in the submodularity and totally balancedness of Chinese postman games with repeated players. Therefore, we focus on sufficient conditions on the assignment of players to edges to ensure submodularity of Chinese postman games with repeated players, independently of the associated travel costs. Moreover, we provide some insights on the difficulty of finding necessary conditions on assignment functions to this end.
Keywords: C71; 330; Chinese postman games with repeated players; balanced game; totally balanced game; submodular game; assignment function